2023
DOI: 10.1136/gutjnl-2022-327853
|View full text |Cite
|
Sign up to set email alerts
|

Acetyltransferase fromAkkermansia muciniphilablunts colorectal tumourigenesis by reprogramming tumour microenvironment

Abstract: ObjectiveThe protein post-translational modification (PTM) in host cells can be rewritten by bacterial enzymes and represents an unprecedented mechanism in the communication between intestinal flora and the host. AlthoughAkkermansia muciniphilahas been widely investigated as a probiotic and blunts colitis-associated tumourigenesis in mice, there is little understanding regarding whetherA. muciniphilais involved in the PTM of colorectal cancer (CRC). This study investigates whether and howA. muciniphilaengages … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 32 publications
(60 reference statements)
1
18
0
Order By: Relevance
“… 70 Additionally, supplementation of Akkermansia mucinophilia suppressed colorectal tumorigenesis in mice models by reprogramming the tumor microenvironment. 71 Similar to these studies, the analysis of ao CRC tumors in our study revealed that Akkermansia was relatively abundant in primary tumors of patients with earlier stages of the disease as compared to metastatic disease, and Akkermansia abundance negatively correlated with tumor size.…”
Section: Discussionsupporting
confidence: 86%
“… 70 Additionally, supplementation of Akkermansia mucinophilia suppressed colorectal tumorigenesis in mice models by reprogramming the tumor microenvironment. 71 Similar to these studies, the analysis of ao CRC tumors in our study revealed that Akkermansia was relatively abundant in primary tumors of patients with earlier stages of the disease as compared to metastatic disease, and Akkermansia abundance negatively correlated with tumor size.…”
Section: Discussionsupporting
confidence: 86%
“…Many species have exhibited therapeutic potential ( Chiva et al, 2002 ; Liu et al, 2020 ). A. muciniphila is a rising probiotic in recent years and has gained wide acknowledgement in different diseases such as obesity ( Depommier et al, 2019 ), colorectal cancer ( Jiang et al, 2023 ) and liver diseases ( Rao et al, 2021 ). Present findings indicate its therapeutic role in early stage in including NAFLD ( Depommier et al, 2019 ; Rao et al, 2021 ) and ALD ( Grander et al, 2020 ), whilst its role in advanced liver cirrhosis has not been detected.…”
Section: Discussionmentioning
confidence: 99%
“…This activation leads to the promotion of tumour invasion and resistance to chemotherapy ( Yang et al, 2020 ). Tumor cells alter their metabolic pathways, such as increasing glycolysis and fatty acid oxidation while suppressing oxidative phosphorylation, in order to fulfil their bioenergy requirements associated with EMT ( Jiang et al, 2023 ).…”
Section: Immunometabolism In the Development Of Colitis Associated Co...mentioning
confidence: 99%